Occurrence and effect of trematode metacercariae in two endangered killifishes from Greece - Kalogianni, Eleni; Kmentová, Nikol; Harris, Eileen; Zimmerman, Brian; Giakoumi, Sofia; Chatzinikolaou, Yorgos; Vanhove, Maarten P M (Parasitology research, 2017)
We report digeneans (Diplostomidae, Crassiphialinae) in the endangered freshwater fishes Valencia letourneuxi and Valencia robertae, endemics of Western Greece. Digenean metacercariae occurred in two forms in the abdominal cavity, excysted and encysted, the latter attached to the gonads, liver and alimentary tract. Parasites were, using morphological and molecular techniques, identified as two representatives of Crassiphialinae, specifically part of the Posthodiplostomum-Ornithodiplostomum clade. The spatial, seasonal, and age class variation in parasite prevalence was examined. Autumn parasite prevalence varied between the six populations sampled (18.2 to 100%). Seasonal prevalence at the two sites sampled quadannually peaked in autumn and reached its lowest value in spring; prevalence increased with size to 100% in young adult fish. We did not find a correlation between prevalence and host sex. Overall parasites' weight averaged 0.64% of the host's, while parasite weight increased with host weight. A comparison of relative condition and hepatosomatic and gonadosomatic indices of infected and metacercariae-free specimens showed that infection did not have a significant effect on host body condition and reproduction. Regarding the parasite's life cycle, planorbid gastropods are proposed as potential first intermediate hosts in view of the host's diet and occurrence data of molluscs in the ecosystem. This is the first record of a diplostomid digenean in valenciid fishes and of representatives of the Posthodiplostomum-Ornithodiplostomum clade in a native Greek freshwater fish. Our findings are discussed in conjunction to fish conservation interventions, since parasites may contribute to the decline of endangered species.
Keywords: Animals; Trematoda; Mollusca; Female; Digenea; infekce červy třídy Trematoda; Trematode Infections; ohrožené druhy; Valenciidae; ženské pohlaví; Greece; Platyhelminthes; nemoci ryb; Fish Diseases; Metacercariae; Killifishes; Planorbidae; Parasite prevalence; stadia vývoje; Fresh Water; Male; metacerkárie; sladká voda; Host body condition; ekosystém; měkkýši; Ecosystem; Cyprinodontidae; Endangered Species; Life Cycle Stages; zvířata; mužské pohlaví; Řecko